A moderated mediation model of green human resource management - Abualigah, Ahmad; Badar, Kamal; Nisar, Qasim Ali; Karatepe, Osman M. (Routledge Journals, Taylor & Francis Ltd, 2024)
Our paper develops and tests a moderated mediation model of green human resource management (HRM). Time-lagged data gathered were utilized to assess climate for green initiative (GI) as a mediator of the impact of green HRM on green voice behavior (GVB) and test green servant leadership (SL) as a moderator of the indirect link of green HRM to GVB via climate for GI. Results from partial least squares structural equation modeling denote that climate for GI partly mediates the linkage between green HRM and GVB. Unexpectedly, green SL reduces the indirect positive relationship of green HRM to GVB via climate for GI. By gauging the aforesaid relationships, our paper augments the existing knowledge regarding the mediating mechanism relating green HRM to GVB. Our paper also augments the green management literature by treating green SL as a moderator.
Keywords: Climate for green initiative; green human resource management; green servant leadership; green voice behavior; hotel workers